Stakeholder analysis and development strategy for the cocoa processing agroindustry in North Luwu District, South Sulawesi, Indonesia - THALIB THALIB; SALENGKE SALENGKE; MAHMUD ACHMAD; KSATRIAWAN ZAENUDDIN; AISYAH TIAR ARSYAD; SAKRAL WIJAYA SAPUTRA (Asian Journal of Agriculture, 2026)
Abstract. Thalib, Salengke, Achmad M, Zaenuddin K, Arsyad AT, Saputra SW. 2026. Stakeholder analysis and development strategy for the cocoa processing agroindustry in North Luwu District, South Sulawesi, Indonesia. Asian J Agric 10 (1): g100113. https://doi.org/10.13057/asianjagric/g100113. Indonesia is one of the world's leading cocoa producers, playing an important role in the national economy. However, its production continues to decline due to climate change, land use change, pest and disease attacks, and limitations in farm management. This study aims to formulate an integrated development strategy for the cocoa processing agroindustry in North Luwu District, South Sulawesi, Indonesia, an area with production potential and favorable agroecological conditions. The research used a mixed-methods approach, including stakeholder analysis, SWOT analysis, and the Analytical Hierarchy Process (AHP). The analysis shows that government actors and the private sector play a dominant role in developing the cocoa agroindustry, while farmer and support institutions serve as system-reinforcing mechanisms. The SWOT analysis placed the cocoa agroindustry in the growth quadrant (S-O), indicating the need for a development strategy that leverages internal strengths to capture external opportunities. Furthermore, the AHP analysis identified investment, raw material quality, and human resource capacity building as priority factors in agroindustry development. The main strategy recommended is to improve product quality and innovation, supported by investment, technology, and strengthening farmer capacity. The implementation of this strategy is expected to sustainably increase productivity, competitiveness, and farmer welfare.